Lipemia after fat loading and atherosclerosis of coronary arteries: correlation of expression - M G Bubnova; D M Aronov; N V Perova; V P Mazaev (Терапевтический архив, 2004)
Aim. To examine relationships between lipemia, atherogenicity of blood lipoproteins spectrum after fat loading (FL) and severity of angiographic manifestations of coronary atherosclerosis. Material and methods. The study enrolled 72 males free of ischemic heart disease (IHD) - group 1; 60 IHD patients with moderate affection of the coronary arteries (CA), i.e. maximal narrowing of one CA 50% - group 2; 107 IHD patients with severe CA affection, i.e. CA narrowing > 50% - group 3. FL was given by J. R. Patsch technique, blood sampling was made before meal, 3 and 6 hours after FL. Results. It was shown that intake of food fats in IHD and IHD-free patients stimulated development of postprandial lipemia of different severity and duration. It appeared due to increased fraction of lipoproteins rich in triglycerides. In group 2 and 3 there was a definite and up to 6 hours in duration postprandial hypertriglyceridemia associated with proatherogenic deviations in lipid and protein components (LDL and HDL) by FL hour 6: growing of LDL cholesterol, apoB, apoB/apoAI and lowering of HDL cholesterol and apoAI. Patients with severe CA atherosclerosis (> 50% narrowing of three CA) had the most severe atherogenic affections in the postprandial lipoprotein spectrum. Conclusion. Postprandial lipemia/hyperthglyceridemia and atherogenic changes in the spectrum of lipoproteins after FL correlate directly with angiographic manifestations of coronary atherosclerosis.